O negro escravo na Paraíba a partir dos inéditos de Ademar Vidal: preposto informacional na construção da memória - Vidal, Fabiano Cesar de Mendonça (2020)
The information which compose personal files carries data from a time and place in the past. When thinking about personal archives, the concepts of memory, identity and information are generally related to this term, finding them relevant fields in modernity. Therefore, in this work the memories of the present seize the archives in search of the historical consciousness registered by the consistency of this memory in a set of unpublished production of Vidal. The general purpose was to analyze the contribution of these writings in the perspective of the construction of memory reguarding the black slave in Paraíba (PB). It is understood that the unpublished produced by Ademar Vidal have the function of being information support, assuming this task according to the circumstance and use. Among various writings of the author, a corpus of three unpublished, which deals with the black slave, is selected. Focusing on the informational context of the archive, located at the Historical and Geographic Institute in Paraíba - IHGP, it presents its organization and analysis as an instrument of construction of a collective memory. The memories of the black slave approached by the author in his writings are part of his collection, which is the set of everything that has social meaning, represented in a material and symbolic way, and must be recovered, preserved, disseminated and socialized. Having this production of the author as the object of study, the documentary research carried out in this work proved to be an essential source of apprehension of reality. The discussion revolved around the constitution of a social memory for the purpose of identifying and legitimizing the information of the unpublished, which in its memorialistic side carry elements capable of strengthening aspects about the period of slavery in Paraíba. The organization attributed to the archive resulted in the conception of this space as an instrument of transmission of a writing, reconstructed by the archive's author / producer. Ademar Vidal's production is considered to have brought to light the contribution of black slaves to official history, giving rise to records of a memory that forces us to rethink another history, in particular, of the Paraibano people.